Modelling infiltration rate impacts on indoor air quality - Roberto San Jose; Juan L. Perez-Camanyo (International Journal of Thermofluids, 2023)
The aim of this work is to better understand the effects of air infiltration on indoor air pollution. A set of simulations has been performed by coupling a building energy demand model with a pollutant transport model in the same EnergyPlus tool. Outdoor pollution and meteorological data are simulated with the WRF/Chem regional air quality and meteorological model, which is an innovative aspect of this work, as the outdoor environment data are taken from monitoring stations far away from the simulated building. The simulations show the behaviour of indoor pollution and energy demand under different types of infiltration rates and how they can affect different areas of the building. There is a strong positive correlation between indoor and outdoor air quality. Infiltration and ventilation increase the annual average NO2 concentration by up to 5.85%. Natural ventilation saves up to 3.24% electricity, but increases heating gas demand by up to 2.28% and NO2 concentration by up to 2.39%.